PENGARUH PENGETAHUAN PERPAJAKAN, SANKSI PAJAK, DAN PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI LINGKUNGAN POLITEKNIK NEGERI CILACAP - Alfarisi Akbar Efendi; Dyah Ayumurni Kartikasari; Nurul Maghfirotul Jannah; Lodis Ramadhan (AKUNTANSI DEWANTARA, 2025)
This study aims to analyze the influence of tax knowledge, tax sanctions, and tax authorities services on individual taxpayer compliance. The type of data used in this study is quantitative data. The quantitative approach is a research method used to examine populations and samples by collecting data using research instruments, analyzing data or statistics with predetermined objectives. The independent variables in this study are tax knowledge, tax sanctions, and tax authorities services. The dependent variable is individual taxpayer compliance. The results of this study indicate that tax knowledge does not affect individual taxpayer compliance. Tax sanctions affect individual taxpayer compliance. Tax authorities services influence individual taxpayer compliance. This study has novelty in terms of time (conducted in 2025), location (Politeknik Negeri Cilacap), respondents (employees at state vocational institutions). Keyword: Tax knowledge; Tax sanctions; Tax authorities services; Taxpayer compliance